Strategi Pembelajaran Seni Gerak Tari di Kelompok B TK Al-Jama’iyah - Nur Hijriyati Waisa; Salsabila Aulia; Winy Wiranti; Astrid Natasya; Hilda Zahra Lubis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research explores the implementation of dance and movement learning in early childhood education at TK Al-Jama’iyah. The study aims to examine the strategies used by teachers, children's participation, and the impact of the activities on child development. Using a qualitative descriptive approach, data were collected through classroom observation, teacher interviews, and documentation. The findings reveal that the learning process emphasizes play-based approaches, utilizing songs, storytelling, movement props, and free expression. Teachers facilitated learning with patience and responsiveness, encouraging participation without coercion. The children actively engaged in the activities, showing increased confidence, creativity, and motor coordination. The study concludes that movement-based dance learning supports holistic development in early childhood and highlights the role of the teacher as a facilitator. This approach can serve as a model for similar institutions seeking to integrate arts-based education in a meaningful and developmentally appropriate way.